Traf2 and NCK Interacting Kinase Is a Critical Regulator of Procollagen I Trafficking and Hepatic Fibrogenesis in Mice - Samuel C. Buchl; Zachary Hanquier; Andrew J. Haak; Yvonne M. Thomason; Robert C. Huebert; Vijay H. Shah; Jessica L. Maiers (Hepatology Communications, 2022)
Hepatic fibrosis is driven by deposition of matrix proteins following liver injury. Hepatic stellate cells (HSCs) drive fibrogenesis, producing matrix proteins, including procollagen I, which matures into collagen I following secretion. Disrupting intracellular procollagen processing and trafficking causes endoplasmic reticulum stress and stress‐induced HSC apoptosis and thus is an attractive antifibrotic strategy. We designed an immunofluorescence‐based small interfering RNA (siRNA) screen to identify procollagen I trafficking regulators, hypothesizing that these proteins could serve as antifibrotic targets. A targeted siRNA screen was performed using immunofluorescence to detect changes in intracellular procollagen I. Tumor necrosis factor receptor associated factor 2 and noncatalytic region of tyrosine kinase‐interacting kinase (TNIK) was identified and interrogated in vitro and in vivo using the TNIK kinase inhibitor NCB‐0846 or RNA interference‐mediated knockdown. Our siRNA screen identified nine genes whose knockdown promoted procollagen I retention, including the serine/threonine kinase TNIK. Genetic deletion or pharmacologic inhibition of TNIK through the small molecule inhibitor NCB‐0846 disrupted procollagen I trafficking and secretion without impacting procollagen I expression. To investigate the role of TNIK in liver fibrogenesis, we analyzed human and murine livers, finding elevated TNIK expression in human cirrhotic livers and increased TNIK expression and kinase activity in both fibrotic mouse livers and activated primary human HSCs. Finally, we tested whether inhibition of TNIK kinase activity could limit fibrogenesis in vivo. Mice receiving NCB‐0846 displayed reduced CCl4‐induced fibrogenesis compared to CCl4 alone, although α‐smooth muscle actin levels were unaltered. Conclusions: Our siRNA screen effectively identified TNIK as a key kinase involved in procollagen I trafficking in vitro and hepatic fibrogenesis in vivo.